Students, Universities and Open Education : Final Report. - Wills, Sandra (Office for Learning and Teaching, 2016)
The project prepared a National Policy Roadmap and evidence-based case studies to support universities in creating, adapting, and incorporating MOOCs and other open education resources (OER) in their technology-based curriculum. The project commenced with the assumption that speculation in MOOCs has temporarily hi-jacked the broader open education agenda. It draws on two recent OLT OER projects by team members and international knowledge of effective open educational practice (OEP) as represented in the reference group to showcase practices that are robust and practically attainable. The partners worked with their students and staff to develop case studies of open, online education including the contribution of our students to co-created curriculum design. In parallel, the OEP Policy Roadmap will recommend national actions for facilitating OEP in Australian university teaching. Drafts will be cascaded to national and international experts for feedback and for additional cases to be mapped to an OER Learning Landscape Framework.